Dwujęzyczność w twórczości Vladimira Nabokova - Mrozik, Maciej (Stylistyka, 2021)
The article is an overview of the way V ladimir Nabokov's multilinguality influenced both the style and content of his works. Among the stylistic devices employed by Nabokov which seem connected to his bilinguality are: code-switching and language-mixing, multilingual glossing, elements ofRussian morphology and syntax in the English works, differentiating of the characters' linguistic competence (from a multilingual perspective), unusual vocabulary, emphasizing the rupture between text and reality through linguistic games (multilingual puns). Nabokov's bilingualism also affects his plots: his works usually have a palimpsestic structure, they are ambiguous in meaning (it is often difficult to say what exactly happened), they contain obsessively returnig themes (mainly that of betrayal and adultery, and of the double). Another important trait is the construction of the protagonist in Nabokov's American novels: it is always someone outside his original linguistic milieu. Statements pertaining to the experience of bilinguality begin to appear in Nabokov's texts after 1938. The Jack of the original as characteristic of the works by many bilingual writers should be noted in connection to Nabokov's own English renderings of his Russian novels (and the Russian version of lolita). Finally, it is interesting to observe in connection to Nabokov's bilingualism that he was perceived in both Russian and American literature as „alien".